2017
DOI: 10.1007/s11356-017-8808-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of atmospheric PAHs and their genotoxicity in petrochemical industrialized Lanzhou valley, northwest China

Abstract: The present study investigated the spatial and seasonal variations and sources of 16 priority polycyclic aromatic hydrocarbons (PAHs) in Lanzhou, a petrochemical industrialized and the capital city of Gansu province, northwest China. The human health risks to these PAHs were assessed using an in vitro genotoxic bioassay technique. Associations among direct genotoxic potency, atmospheric PAH concentrations, and potential carcinogen risks were examined. Due to high PAH emissions from fossil fuel combustion and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Atmospheric PAHs, primarily derived from anthropogenic activities such as industrial operations, vehicle exhausts, refineries, waste incineration and domestic heating, are emitted by incomplete combustion of organic matters at high temperatures [ 9 ]. Numerous international studies in petrochemical industrial areas and oil refineries have tracked particulate contamination and severe particulate PAH emissions [ 10 , 11 , 12 , 13 , 14 ]. Nevertheless, the adverse health effects on children living in nearby industrial areas have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric PAHs, primarily derived from anthropogenic activities such as industrial operations, vehicle exhausts, refineries, waste incineration and domestic heating, are emitted by incomplete combustion of organic matters at high temperatures [ 9 ]. Numerous international studies in petrochemical industrial areas and oil refineries have tracked particulate contamination and severe particulate PAH emissions [ 10 , 11 , 12 , 13 , 14 ]. Nevertheless, the adverse health effects on children living in nearby industrial areas have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the risks associated with inhalation of PAHs are higher in winter compared to summer. , The highest cancer risk was found in several provinces in urban/suburban China. For example, values for the samples collected in the winter in Hefei, China, reached 5.1 × 10 –4 . ,, …”
Section: Resultsmentioning
confidence: 98%
“…For example, values for the samples collected in the winter in Hefei, China, reached 5.1 × 10 −4 . 68,72,73 For source-related risks, the LLCR profile is very different from the factor contribution of PMF modeling. For example, coal combustion contributed to the highest proportion of total PAH concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous research on the PAH-degrading bacteria in the phylloplane has demonstrated the presence of the following bacteria: Alcaligenes , Bacillus , Serratia [ 23 ], Sphingomonas , Pseudomonas [ 24 ], Microbacterium , Rhizobium , Deinococcus spp. [ 5 , 13 , 25 ], and Mycobacterium [ 14 , 15 ]. The role of these bacteria in the degradation of the PAHs in soils has been extensively studied [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%